Arabic Grammatical Errors in Translating Islamic Texts Among Tarjamah Students - Yupi Desfina; Konul Babayeva; Maryam Nawaf Al Dhahab (Journal of Language, Literature, and Educational Research, 2026)
Purpose of the study: This study aims to identify common Arabic grammatical errors made by eighth-semester Tarjamah students in translating Islamic texts and to analyze the factors influencing these errors in Arabic-to-Indonesian translation practices. Methodology: This study employed a qualitative field research design combined with library research. Data were collected through questionnaires, interviews, translation tests, documentation, and literature review involving eighth-semester Tarjamah students of State Islamic University Syarif Hidayatullah Jakarta. Data analysis techniques included editing, tabulating, classification, and grammatical error analysis focusing on nahwu and sharaf aspects in Islamic text translation. Main Findings: The findings revealed that many students still experienced difficulties in applying Arabic grammar rules, particularly nahwu and sharaf, during the translation process. Frequent errors were found in identifying fi’il-fa’il structures, jumlah ismiyyah and fi’liyyah, mudhaf-mudhaf ilaih, and grammatical sentence positions. These weaknesses affected translation accuracy, coherence, and naturalness. Internal learning motivation, limited practice, instructional methods, and insufficient mastery of qawa’id were identified as major contributing factors. Novelty/Originality of this study: This study specifically examines Arabic grammatical errors in translating Islamic manuscripts among Tarjamah students using authentic translation tasks from Jâmi’ al-Fiqih texts. The research contributes new insights into the relationship between Arabic grammar mastery and translation quality while highlighting pedagogical weaknesses in Arabic grammar instruction within higher education translation programs.